2021
DOI: 10.1021/acschemneuro.1c00140
|View full text |Cite
|
Sign up to set email alerts
|

Binding Mechanisms of Amyloid-like Peptides to Lipid Bilayers and Effects of Divalent Cations

Abstract: In several neurodegenerative diseases, cell toxicity can emerge from damage produced by amyloid aggregates to lipid membranes. The details accounting for this damage are poorly understood including how individual amyloid peptides interact with phospholipid membranes before aggregation. Here, we use all-atom molecular dynamics simulations to investigate the molecular mechanisms accounting for amyloid−membrane interactions and the role played by calcium ions in this interaction. Model peptides known to self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 75 publications
2
33
0
Order By: Relevance
“…Amphipathic peptides with sequence that alternates strictly between non-polar (i.e., phenylalanine F) and charged amino acids (i.e., positive lysine K, and negative glutamic acid E), that is, Ac-(FKFE) 2 -NH 2 , is used to study membrane damage. Experimental studies have shown that this peptide self-assembles into amyloid fibrils forming supramolecular nanotubes. ,, In all-atom simulations, this peptide was also shown to self-assemble into amyloid-like fibrils and to interact with lipid membranes in a computationally accessible time-frame. , Here, membrane damage is studied using three anionic membranes made by combining zwitterionic, that is, 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphocholine (POPC), 1,2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC), and 1,2-dimyristoyl- sn -glycero-3-phosphocholine (DMPC), with anionic lipids, that is, 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphoglycerol (POPG), 1,2-dipalmitoyl- sn -glycero-3-phosphoglycerol (DPPG), and 1,2-dimyristoyl- sn -glycero-3-phosphoglycerol (DMPG). The lipid composition of the three membranes studied here are 7:3 POPC/POPG, 7:3 DPPC/DPPG, and 7:3 DMPC/DMPG.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amphipathic peptides with sequence that alternates strictly between non-polar (i.e., phenylalanine F) and charged amino acids (i.e., positive lysine K, and negative glutamic acid E), that is, Ac-(FKFE) 2 -NH 2 , is used to study membrane damage. Experimental studies have shown that this peptide self-assembles into amyloid fibrils forming supramolecular nanotubes. ,, In all-atom simulations, this peptide was also shown to self-assemble into amyloid-like fibrils and to interact with lipid membranes in a computationally accessible time-frame. , Here, membrane damage is studied using three anionic membranes made by combining zwitterionic, that is, 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphocholine (POPC), 1,2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC), and 1,2-dimyristoyl- sn -glycero-3-phosphocholine (DMPC), with anionic lipids, that is, 1-palmitoyl-2-oleoyl- sn -glycero-3-phosphoglycerol (POPG), 1,2-dipalmitoyl- sn -glycero-3-phosphoglycerol (DPPG), and 1,2-dimyristoyl- sn -glycero-3-phosphoglycerol (DMPG). The lipid composition of the three membranes studied here are 7:3 POPC/POPG, 7:3 DPPC/DPPG, and 7:3 DMPC/DMPG.…”
Section: Methodsmentioning
confidence: 99%
“…This can be explained by favorable interactions between atoms of lipid tails and nonpolar side chains. These interactions, which hold peptides anchored on the membrane surface, 60,65 also induce distortions in the lipid tail as depicted in panel m. The latter panel highlights selected lipids that are close to β-sheets before poration. Notice that acyl tails of those lipids are almost parallel to the membrane surface filling the void in the bilayer beneath β-sheets 66 and maximizing their interactions with phenylalanine side chains.…”
Section: This Quantity Is Defined Asmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is affected by specific lipids including cholesterol, sphingomyelin, and gangliosides [717,718]: lipid types typically present in the outer leaflet of the cell membrane. Amyloid fibers at a membrane surface have thus been frequently studied using MD simulations, e.g., [719][720][721][722][723][724][725][726][727][728][729][730], however, a surprisingly small fraction of this work has been performed in the context of drug design [731,732]. Khondker et al, proposed designing drugs with a mode of action that involved modulating membrane properties to affect the aggregation of amyloid-β25-35 at the bilayer surface [229].…”
Section: Can Drugs Prevent Amyloid Formation Via the Modification Of Membrane Properties?mentioning
confidence: 99%
“…This is in agreement with previous work that identified electrostatic interactions to be particularly important for cationic peptides and hydrophobic peptide residues to drive the interactions of nonpolar residues with membranes. 66,116 The sequence and number of positively charged residues in peptides, such as arginine and lysine, may thus have important influence on the degree and direction in which anionic and oxidized lipids affect peptide aggregation.…”
Section: Charge At Ph 74mentioning
confidence: 99%